Rural in‐migration and agricultural development: Evidence from Zambia - Chamberlin, Jordan; Jayne, T. S.; Sitko, Nicholas J. (International Association of Agricultural Economists, 2020)
While a considerable body of literature has developed in recent years around the drivers and consequences of rural out‐migration in sub‐Saharan Africa, relatively little work has been done to understand the impacts of migration into rural areas. We use nationally representative household survey data from Zambia to explore the relationship between rural in‐migration and agricultural productivity outcomes in receiving communities. We document high levels of rural in‐migration throughout Zambia—12% of rural household heads having moved from elsewhere within the previous 10 years—with two‐thirds of rural in‐migrants originating from other rural areas. Migrants are, on average, better endowed with capital resources than their nonmigrant neighbors and are more engaged with input and output markets. After controlling for other factors, we find that higher rates of rural in‐migration are associated with greater agricultural productivity outcomes in receiving communities. These positive associations are particularly pronounced in more remote rural areas, and where in‐migration originates from other rural areas. Taken together, our results suggest that rural in‐migrants play an important role in the rural transformation processes underway in Zambia.